(untitled) (Research, Society and Development, 2024)
Facial skin pigmentation is one of the most prominent visible features in everyday interactions and often influences the perception of beauty. There is currently no evidence on how facial pigmentation spots can influence aesthetic perception. The objective was to evaluate the perception of aesthetics and the attractiveness of smiling photos with the presence of facial pigmentation spots in different locations on the face. Four images of the smiling face were used in the frontal pattern, standardized and modified with the help of Photoshop®: no pigmentation spots, spots below the right perioral region, above the upper left perioral region, and in both the lower right region and upper left region of the face. The Eye-tribe hardware and Ogama software were used for eye-tracking, and a questionnaire with two questions — “Judging aesthetic aspects, do you consider this person attractive and beautiful?” and “What stood out the most about this image?” were applied to laypeople observers with a word cloud typed on the Mentimeter. The dot maps showed that in all pigmentation spots positions, the right eye and the smile in the area of the central incisors attracted the most attention of laypeople. The smile was the most cited, with emphasis on the words ’eyes’ and ’teeth’ in Mentimeter. Facial pigmentation spots in different locations did not interfere with aesthetic perception. The face without the presence of nevi was considered the most attractive, and the smile, teeth, and eyes were the structures that most caught the attention of the laypeople.